A39 NOVEL GAIN OF FUNCTION NON-RECEPTOR TYROSINE KINASE MUTATIONS ARE LINKED TO THE PATHOGENESIS OF VEOIBD. (26th February 2020) - Mehta, M; Wang, L; Guo, C; Warner, N; Li, Q; Pan, J; Boztug, K; Uhlig, H; Muise, A
Abstract: Background: Very early-onset inflammatory bowel disease (VEOIBD) is an emerging global disease, that results in inflammation of the digestive tract. Severe forms of VEOIBD can be caused by mutations in a single gene (monogenic variants) and, can result in death. A candidate gene which codes for a non-receptor tyrosine kinase (nRTK) has recently been implicated as a monogenic cause of IBD (unpublished). Whole exome sequencing was performed in two unrelated children who presented with symptoms of IBD identifying two distinct de novo gain of function mutations ( S550Y and P342T ). Both mutations are located in the highly conserved region of the nRTK, and were predicted to have similar downstream effects. Furthermore, four other patients with a variety of adult-onset immune disorders have recently been identified with rare variants in the same gene ( M450I, R42P, A353T, V433M, S550F ) but, their potential gain of function status remains to be determined. Studies show that this nRTK is an essential mediator in inflammation. It is expressed in both intestinal epithelial and immune cells however, its role in infantile IBD is unclear. This protein is first activated by phosphorylation and is linked to activating downstream transcription factors such as ERK and JNK. All these target proteins play a meaningful role in intestinal inflammation in patients with IBD. Aims: Since we identified P342T and S550Y to be gain of function, we wanted to determine if the new variants exhibit a similar downstream impact on target protein expression levels when compared with S550Y and P342T . We also wanted to identify if all variants can be rescued with a known nRTK inhibitor. It is hypothesized that the new variants are gain of function and that all variants can be rescued with the inhibitor. Methods: Using western blot analysis, the activation of ERK, JNK and nRTK was compared between wildtype (WT) and mutants. This in vitro method helped identify the degree of activation. For the second part of the study, HEK293T cells were treated with inhibitor to test for a rescue of phenotypes via western blot analysis. Results: Results show an increased activation of nRTK, ERK and JNK in all variants with S550Y and S550F having the highest activation. Furthermore, pharmacological inhibition using small molecular kinase inhibitors resulted in decreased activation of nRTK, ERK and JNK suggesting a rescue of phenotypes. Conclusions: Characterizing the downstream functional impact of these nRTK variants is an important first step to determine if gain of function nRTK mutations drive IBD. With a rising prevalence of IBD worldwide, these findings may lead to the development of pharmacological nRTK inhibitors as a novel personalized therapeutic approach for these patients and possibly for the broader IBD population. Funding Agencies: CIHR